If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(y + 9) = 8y + -7 Reorder the terms: 9(9 + y) = 8y + -7 (9 * 9 + y * 9) = 8y + -7 (81 + 9y) = 8y + -7 Reorder the terms: 81 + 9y = -7 + 8y Solving 81 + 9y = -7 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 81 + 9y + -8y = -7 + 8y + -8y Combine like terms: 9y + -8y = 1y 81 + 1y = -7 + 8y + -8y Combine like terms: 8y + -8y = 0 81 + 1y = -7 + 0 81 + 1y = -7 Add '-81' to each side of the equation. 81 + -81 + 1y = -7 + -81 Combine like terms: 81 + -81 = 0 0 + 1y = -7 + -81 1y = -7 + -81 Combine like terms: -7 + -81 = -88 1y = -88 Divide each side by '1'. y = -88 Simplifying y = -88
| 6b^2-11b-35=0 | | -(b+1)=10-b | | 6a+3=-3(2a-1) | | 4x-10-6x+3=5-9x-7+2x | | 1500+8x=1500+12x | | 106-21.20= | | 6p=3(t+4)-t | | 8x^2-13=-8 | | 22-(x+5)=7x-7 | | 4x-14-6x+4=6-8x-8+2x | | 3y-5=5y+4 | | 6m^2+5m-4= | | 5d-d= | | 21.20-106= | | 4m^2+5=-57 | | 4x+39+12x-17=180 | | x+x+11=83 | | 7y-13-4y+8=0 | | A+1=37+a | | 7x^2+0.5x=0 | | 6x-5=18x+1 | | -20+17g=1-g | | 5p^2+4=429 | | x+x+7=65 | | 3w-1=6w-5 | | .5(4x+4)-(x-8)= | | 7(9+4x)=-105 | | 7x^2+.5x=0 | | 2(9)+(3)= | | 28=3(1+x)+5(-x+5) | | 8+5x=52x | | x^12*x-8=0 |